PENGARUH LATIHAN PERNAPASAN PURSED LIPS DAN POSISI SEMI FOWLER TERHADAP PERUBAHAN SESAK PADA PASIEN PPOK - Belinda Zahara Dewi; Dahrizal Dahrizal; Rahma Annisa (JURNAL PENELITIAN TERAPAN KESEHATAN, 2021)
Chronic obstructive pulmonary disease (COPD) is a number of disorders that affect the movement of air from and out of the lungs which is characterized by a continuous blockage of air flow from the lungs. This blockage of air flow is progressive and is related to the pulmonary inflammatory response. The use of pursed lips and semi-fowler positions will make it easier for nurses to reduce tightness in COPD patients. The purpose of knowing the effect of pursed lips breathing and semi-fowler position on changes in shortness in COPD patients. The research design used in this study was a quasi-experimental design with a pretest-posttest with control group design. The sampling technique used in this study was a consequtivesampling technique with 20 people in one group. The analysis used is non-parametric using mannwhitney. The results showed there was an effect of pursed lips breathing exercises and semi-fowler position on changes in tightness in COPD patients (P = 0.005). Sweet solution is a method can be used or done to reduce tightness in COPD patient.